Investing in tomorrow's natural resource stewards: how understanding target audiences can improve efforts to reconnect youth with nature - Thomas, Rebecca, author; Teel, Tara, advisor; Bruyere, Brett, committee member; Davies, Timothy, committee member (Colorado State University. Libraries, 2012)
This thesis presents two manuscripts that explored how conservation education efforts could be improved through development of more targeted educational initiatives informed by research. The overall research and outreach initiative, upon which these manuscripts were based, encompassed the ideals of the "No Child Left Inside" movement, which grew in part from Richard Louv's (2008) best-selling book Last Child in the Woods. Underlying this movement are linkages between time spent outside as a child and overall mental and physical health and well- being as well as future commitment to environmental stewardship. Broad scale societal and demographic changes (e.g., urbanization, economic growth, increasing levels of income and education, and population growth, among others) impact how children and families interact with nature. Environmental education can contribute to addressing these changes by facilitating interactions with nature. The overall purpose of this thesis was to evaluate environmental education programs offered by state fish and wildlife agencies that would account for public values toward wildlife by reaching out to diverse target audiences, making both methodological and theoretical contributions to the field of environmental education. The purpose of the first paper was to evaluate the Lincoln Safari, an established, successful program developed to encourage families to explore natural and cultural heritage sites within an urban area. The objectives of evaluating this program were to 1) assess the diversity of participants in the program in terms of their values toward wildlife, 2) document how participating in the Lincoln Safari influenced conservation behaviors, and 3) understand key elements that attracted families to participate in the Lincoln Safari. Data were collected via a mixed-methods approach that included an on-site survey administered to participants in the 2010 Lincoln Safari program in Lincoln, Nebraska, monthly follow-up surveys administered via e- mail, and focus group interviews with a select group of participating families. Results indicated that the Lincoln Safari has been successful in attracting a variety of age groups and wildlife value orientation types. Quantitative analysis of engagement in environmental stewardship behaviors showed that there was a link between the number of years a family had participated in the Lincoln Safari and the amount of time they reported spending outdoors as a family over the past year as well as their engagement in recycling behaviors. Furthermore, individuals with certain value orientations toward wildlife were more likely than others to report increases in other environmental stewardship behaviors. Focus group interviews corroborated these findings, revealing, for example, that Lincoln Safari participation resulted in increased mindfulness of the environmental impact of daily decisions. Additionally, these focus group interviews revealed elements of the Lincoln Safari that made it particularly appealing to families. Overall, families found it attractive because it awakened a sense of adventure, facilitated multigenerational learning, and helped families to create memories. The second paper documents a methodological approach for studying outcomes of youth participation in an environmental education program that included service learning and integration of cultural heritage values in the Ka`u region of the Island of Hawai`i. The purpose of this study was to learn about how the integration of cultural heritage values into the program affected how participants related to nature, and to develop a methodological approach for evaluating environmental education programs for underserved groups in culturally sensitive areas. This study was based in part upon previously conducted interviews with key elders in the community that highlighted the importance of building upon existing partnerships, working with local residents already connected within the community, and integrating cultural heritage values into environmental education programs in Ka`u in order to maximize interest and participation in programs in this region. Researcher observations, photovoice, document analysis and semi- structured interviews were then used to assess a recent 2011 offering of the Imi Pono No Ka Aina (Seeking Excellence for the Land) program in Ka`u. Participants' program portfolios, which consisted of participants' written program materials, researcher observations, photographs and interview transcriptions, were analyzed to better understand the impact of the program on participants' views of nature and wildlife. Analysis showed that incorporating cultural heritage values into the Imi Pono no ka Aina program in Ka`u was successful in connecting Hawai`ian youth from Ka`u to nature, and that employing a mix of qualitative methodologies yielded a more holistic understanding of the participants' experiences than relying on a single data source.
Keywords: experiential education; Hawaii; nature education; place based education; traditional ecological knowledge; wildlife value orientations